Prophylaxis of hepatic encephalopathy: current and future drug targets - Maharshi, Sudhir; Sharma, Barjesh Chander (Hepatology international, 2024)
Hepatic encephalopathy is described by a broad spectrum of neurological and psychiatric aberrations resulting due to advanced liver dysfunction. It is a neurological disorder due to hepatic insufficiency and/or portosystemic shunts. Its clinical presentation includes neuropsychiatric dysfunction ranging from subclinical changes to comatose state. It is a sign of poor prognosis in cirrhotics with a high 1-year mortality. Each episode of hepatic encephalopathy leads to high hospitalization rate, poor prognosis and raised burden of healthcare. Primary prophylaxis is prevention of initial occurrence and secondary prophylaxis is prevention of reappearance of hepatic encephalopathy in subjects who had prior history. Early detection and management of triggers is very important in the treatment of hepatic encephalopathy. The initial choice of treatment is still lactulose, as it is effective in minimal, overt, and recurrent hepatic encephalopathy. Rifaximin is equally effective as lactulose in managing hepatic encephalopathy and is better tolerated. Branch chain amino acids are beneficial in subjects who are protein intolerant. L-ornithine L-aspartate and probiotics are also useful in the management of hepatic encephalopathy. Rifaximin along with lactulose is effective in managing overt and recurrent hepatic encephalopathy. Large portosystemic shunts embolization and liver transplant is efficacious in certain group of patients. Nutritional therapy and fecal microbiota transplantation are newer therapies for hepatic encephalopathy but the evidences are limited, more research is required to prove their efficacy. Involvement of hospital pharmacists, telemedicine, and providing education are also beneficial in managing hepatic encephalopathy.